PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE GI (GROUP INVESTIGATION) TERHADAP MOTIVASI BELAJAR SISWA SMA NEGERI 1 KINTAMANI - Ni Wayan Budiani; I Made Diarta (Fakultas Keguruan dan Ilmu Pendidikan (FKIP) Universitas Mahasaraswati Denpasar, 2014)
The study was conducted to know the influence of implementing Cooperative Learning Model Group Investigation (GI) type toward students’ motivation in learning. It was done by using batur Lake Geopark as the learning site. Design of the study is Non Equivalent pretest-posttest control group. The subject was all grade ten students of SMA Negeri 1 Kintamani in academic year 2012/2013. Through systematic sampling technique, there were 21 students for control group and 20 students for experiment group. The data was gathered by using quiestionaire, and then analyzed with non parametric statistics: Mann Whitney U Test. The results showed that there is a significant influence toward students’ learning motivation after having GI, around 254.11, sd= 14.1.